A comparative analysis of rectangular cut edge patch antenna on various substrate - Choudhury, Sachidananda; Kalyani, Veeranki; Sai Teja, R; Sreenivasan, P; K. Kotamraju, Sarat; Ch. Sri Kavya, K (International Journal of Engineering and Technology, 2017)
An analysis of simple microstrip patch antenna has been designed which comprises of various dielectric substrates that is placed in between metallic patch and ground. Substrates used in this design Epoxy (FR4), Rogers duroid 6002 (tm) with various relative permittivity 2.94 and 2.2 and thickness of 3.2mm. Some applications for the designed frequency are wireless fidelity, WLAN application, Bluetooth. The proposed antenna is designed in HFSSV15 Software operating at 2.4 GHz frequency which renders return loss not more than -10dB. The purpose of this paper was analyzation and simulation for the designed antenna with various parameters like gain, peak gain, efficiency, return loss, band-width when the structure and substrate changes.